Instantaneous petroleum charge in the Shunbei reservoirs, Tarim Basin - Wang, Qianru; Huang, Haiping; Jiang, Tao (Frontiers in Marine Science, 2025)
Instantaneous petroleum charge is uncommon in sedimentary basins, particularly in the Tarim Basin, where petroleum has accumulated from multiple source rocks with multiple episode charge stages. In the present study, an instantaneous petroleum charge was identified within the No.3 fault zone of the Shunbei reservoirs in the Tarim Basin. The oil from Well Shunbei 3 (SHB3 oil) is considered as an end member close to the stratigraphic maturity of source rock at a certain maturity level with evidence from n-alkanes, isoprenoids, steroids, terpenoids, diamondoids and a series of aromatic hydrocarbons. In comparison to oil samples from the No.1 fault zone, SHB3 oil did not receive the early-charged oil whereas it has not undergone petroleum charging during the very late maturation stages. The end member of instantaneous petroleum charge in Shunbei reservoirs provides valuable insights into petroleum generation, expulsion and charge histories of ultra-deep Ordovician reservoirs in the Tarim Basin.